'Til heist do us part - Desai, Sara (Berkley Romance, 2024)
"Diamond necklaces, billionaires, Mafia bosses, and student loans--it's all in a day's work for Simi Chopra and her ragtag heist crew in the next romantic-comedy caper from Sara Desai. It's been a year since Simi Chopra's motley crew pulled off a high-wire diamond necklace heist with the help of sexy rogue Jack Danger. After living it up on the reward money, they're back where they started, struggling to pay their bills. So when a Chicago Mafia boss demands they return the jewels--plus interest, or else--they need to get the team back together... and fast. Unfortunately, Simi soon discovers that the necklace is in the hands of Jack's nemesis, a highly-skilled and supremely vengeful master thief who is not above a little blackmail to get even. (Did Jack really have to piss her off?) Now, the crew is forced into her working her con in order to get the necklace back. As if Simi needed any more complications while trying to rob a billionaire's mansion, she and Jack are on the rocks, someone else is after her score, and a gorgeous detective is hot on her tail. Simi better be careful or she'll end up in the less fun kind of handcuffs"--